Illustrated invertebrate anatomy : a laboratory guide - Pierce, Sidney K (Oxford University Press, 1987)
Using state-of-the-art photographic techniques, this atlas contains detailed anatomical and morphological photomicrographs and electron micrographs of marine, freshwater, and terrestrial invertebrate organisms. Each specimen is shown intact and expertly dissected, accompanied by extensively labelled line drawings and comprehensive instructions. The book will be an invaluable aid in laboratory courses for invertebrate zoology. It has been especially designed as a flexible supplement to laboratory demonstrations, one that presents the species that students are likely to encounter in a teaching laboratory, regardless of the instructor's particular emphasis or approach.